PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PT.EKA DURA INDONESIA (PALM OIL MILL)ROKAN HULU - ", Septiarisa; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at PT.Eka Dura Indonesia (PALM OIL MILL)RokanHulu located in Kunto Darussalam District of RokanHulu Regency. This study aims todetermine the influence of organizational culture and job satisfaction on the performance ofemployees of PT.Eka Dura Indonesia (PALM OIL MILL) RokanHulu.In this research the method used is descriptive quantitative with SPSS programver. 23for windows.The population in this research is all employees of production part of PT.EkaDura Indonesia (PALM OIL MILL) RokanHulu in Kunto Darussalam District RokanHuluRegency which amounted to 171 employees. The sample in this research is taken by usingproportional random sampling method that is 63 employees. Methods of data collectionusing questionnaires and free interviews. Hypothesis testing using multiple linear analysismethod with result of research that is Y= 4,165+0,176X1+0,505X2.The research that has been done show the result that the respondent's response toorganizational culture, job satisfaction and employee performance in good category. Whilefor the T test that has been done shows that the variable of organizational culture and jobsatisfaction partially significant effect on employee performance.And F test results show thatsimultaneously organizational culture and job satisfaction employee. And for calculation ofcoefficient of determination (R2) obtained value of R Square equal to 0,713 to employeeperformance.This shows that organizational culture and job satisfaction give effect of 71,3%on employee performance, while the rest 28,7% influenced by other variable not examined inthis research.Keywords: Employee Performance, Job Satisfaction,Organizational Culture.